2017
DOI: 10.1007/s11605-017-3440-z
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Cancer Presenting with Jaundice: Uniformly Fatal or Still Potentially Curable?

Abstract: Background Jaundice as a presenting symptom of gallbladder cancer has traditionally been considered to be a sign of advanced disease, inoperability, and poor outcome. However, recent studies have demonstrated that a small subset of these patients can undergo resection with curative intent. Methods Patients with gallbladder cancer managed surgically from 2000–2014 in 10 US academic institutions were stratified based on the presence of jaundice at presentation (defined as bilirubin ≥ 4 mg/ml or requiring preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
(41 reference statements)
2
26
0
Order By: Relevance
“…Among the 168 studies that met the initial search criteria, eight studies [9][10][11][12][13][14][15][16] were selected for the meta-analysis. Figure 1…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 168 studies that met the initial search criteria, eight studies [9][10][11][12][13][14][15][16] were selected for the meta-analysis. Figure 1…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [9][10][11][12][13][14]16 consisting of 1960 participants reported overall survival. Overall survival was significantly worse among patients who presented with jaundice, compared with patients who did not (HR: 2.21, 95% CI, 1.64-2.97; P < 0.001).…”
Section: Overall Survival In Resected Patientsmentioning
confidence: 99%
See 3 more Smart Citations